Da experiência artística a poética docente: discussões acerca de ações estratégicas e táticas de artistas/docentes no ensino universitário de teatro - Araújo, Valéria Gianechini de (2014)
The work goes from the contemporary concept of artist-teacher in order to define and discuss the working ways and possibilities for the artist who teaches in the context of the University courses of Art in Brasil, specifically Theatre courses. Thus, the work uses examples and experiences of the actress and teacher Ana Maria Pacheco Carneiro, as to define forms of being and working of the artist inside brasilian university art courses, through their practices in class and in the transposition of the artistic experiences to the teaching.The work discusses the notion of artist-teacher, at first in a conceptual and terminological approach, for then broaden it and propose dialogs between different points of view concerning the contemporary relations between arts and teaching. It can not be ignored, also, how my own experience in acting and teaching directs and particularizes the discussion.The experiences collected among some teaching artists led to a discussion supported in part by the writings of Michel de Certau, mainly his notions of tactics and strategy. These concepts supported the understanding, here expressed, of the artsist´s actions inside the learning institutions, and acts as a touchstone for the selection as for the discussion of the precedures and postures assumed by the teaching artists studied, such as Tácito Borralho, Adriana Schneider Alcure, besides Ana Carneiro.